If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 4n = 1 + 5n Solving -3 + 4n = 1 + 5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5n' to each side of the equation. -3 + 4n + -5n = 1 + 5n + -5n Combine like terms: 4n + -5n = -1n -3 + -1n = 1 + 5n + -5n Combine like terms: 5n + -5n = 0 -3 + -1n = 1 + 0 -3 + -1n = 1 Add '3' to each side of the equation. -3 + 3 + -1n = 1 + 3 Combine like terms: -3 + 3 = 0 0 + -1n = 1 + 3 -1n = 1 + 3 Combine like terms: 1 + 3 = 4 -1n = 4 Divide each side by '-1'. n = -4 Simplifying n = -4
| 4x+36+3x-3=180 | | 3.2k+0.17=5.76 | | (x+5)-(2x+3)=0 | | -5x-7=3+5x | | -3(1+8x)=23+2n | | -2x-15-2x= | | 5-n=-3n+5 | | 8x+5=2x+7 | | R=26x | | X*1+X= | | 26=15+v | | c/5=-11/6 | | -15x+11x-3=1-5(x+1) | | 3(y+6)=2y-2 | | 6=0x | | x+(x+1)=(x+2)-(x-1) | | 3-t/6=7 | | C=81000+18x | | 11a+9a=4a+30 | | 5w^2-2w+3=0 | | x^2+18x+90x=0 | | (7t-3)-(3t+1)=-3(1-3t) | | -2-42=x | | 5.60+.25x=19.85 | | 45x-11=250 | | 2x^2+16x+5= | | x*x+12x+32=0 | | 5(3p-5)+4p=5p-6(p+4) | | 14*30b=-196 | | 176-0.8a=122+a | | 5x+2(3x-4)=80 | | 8x+4y=22 |